A hybrid PV/utility powered irrigation water pumping system for rural agricultural areas. Issue 1 (1st January 2018) - Hassan, Waqas; Kamran, Farrukh
Abstract: Pakistan is primarily an agriculture country with the capability of producing wheat, cotton, sugarcane and rice, which together are more than 75% of the total crop output. Underground water is the main source of irrigation. Most of the water pumps use diesel generator while others run on electricity. The diesel is very expensive and electric supply situation is very unreliable in Pakistan. Photovoltaic (PV) powered water pumps are an attractive alternative solution, but due to the high cost of solar panels, they are not within the reach of a common farmer. In this paper, a novel architecture for an irrigation water pump, simultaneously powered by utility and PV panels, is proposed. No battery backup is required. The system employs maximum power point tracking. The pump controller receives a single control input to produce desired water flow rate and concurrently maximizing the utilization of PV resource. The proposed solution allows the farmer to incrementally add solar panels to an existing grid powered pumping system, thereby reducing the initial investment required for full solar deployment. The investment in the partial deployment of solar panels is paid back to the farmer in reduced electricity tariff.